TNF-alpha modulates the differentiation induced by butyrate in the HT-29 human colon adenocarcinoma cell line - Kovaríková, M; Pacherník, J; Hofmanová, J; Zadák, Z; Kozubík, A (European journal of cancer (Oxford, England, 2000)
The aim of this study was to determine whether and how tumour necrosis factor alpha (TNF-alpha) modulates butyrate effects. After the treatment of human colon adenocarcinoma HT-29 cells with sodium butyrate (NaBt), TNF-alpha or with their combinations we detected cell cycle (flow cytometry), cell proliferation (amidoblack and MTT assays), the amount of dead (floating) and apoptotic cells (flow cytometry and fluorescence microscopy), and the level of differentiation by alkaline phosphatase (ALP) activity (spectrophotometry), relative F-actin content (confocal laser scanning microscopy analysis) and E-cadherin expression (Western blot analysis). Both TNF-alpha and NaBt decreased cell growth in a dose-dependent manner. After combined treatment of the cells with both agents used, either none or additive effects were observed as compared with NaBt treatment alone. The level of dead and apoptotic cells was dose-dependently increased after this combined treatment. In contrast, TNF-alpha suppressed ALP activity and F-actin accumulation induced by NaBt. The results suggest that TNF-alpha does not influence significantly the antiproliferative effects of NaBt but, contrary to its potentiation of apoptosis, it markedly reduces NaBt-induced differentiation of HT-29 colon adenocarcinoma cells.
Keywords: kadheriny; Cell Transformation, Neoplastic; apoptóza; TNF-alfa; Tumor Necrosis Factor-alpha; Alkaline Phosphatase; HT29 Cells; nádorové proteiny; Humans; Neoplasm Proteins; lidé; Butyrates; alkalická fosfatasa; butyráty; Apoptosis; nádorová transformace buněk; buňky HT-29; Cadherins